(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The article analyses the intersection of law, medicine and language in the regulation of medical devices, particularly during the COVID-19 pandemic. It examines how the global health crisis has highlighted the complexities of translating medical and legal terminology, adapting regulatory frameworks and ensuring the safe use of these devices. Through the lens of medico-legal translation, the paper discusses the challenges of adapting medical concepts to legal contexts.